ByzRev 01.2019.008: Apostolos Karpozilos – Georgios Fatouros (eds), The Letters of Theodoros Hyrtakenos.: Greek Text, Translation, and Commentary. Athens: Kanakis 2017. - Grünbart, Michael (The Byzantine Review, 2019)
Apostolos Karpozilos – Georgios Fatouros (eds), The Letters of Theodoros Hyrtakenos. Greek Text, Translation, and Commentary. Athens: Kanakis 2017. 400 S. – ISBN 978-960-6736-22-3 (€ 21.40)